Prognostic value with intervertebral herniation disk disease in dogs - Jeong, In-Seong; Rahman, Md. Mahbubur; Kim, Hwangmin; Lee, Gi-Jong; Seo, Beom-Seok; Choi, Gab-Chol; Kim, Sehoon; Kim, Namsoo (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The objective of this retrospective study was to evaluate the preoperative clinical characteristics to predict postoperative neurologic recovery in dogs with intervertebral herniated disk disease (IVDD). Materials and Methods: The dogs were classified according to postoperative neurologic recovery from clinical history of the hospital e-book. Excellent when dogs (n=13) were neurologically normal; good (n=8) when postoperative neurologic grade was improved from preoperative condition had improved sufficiently to require no or minor therapy after discharge; fair (n=4) is considered when postoperative neurologic status was unchanged from preoperative condition and poor (n=5) when major postoperative complication developed as a consequences neurologic grade had worsened at discharge than their preoperative score or the patient died. The evaluated preoperative clinical characteristics in all groups are breed, age, sex, duration of clinical sings appearance (DCSA), preoperative neurologic grading system (PNGS), compression rate (pre and post-operative) in MRI and CT scan, housefield unit (HU), type of IVDD and surgical procedures, and compared with excellent group. Results: no definitive relationship was found between the clinical characteristics and neurologic recovery, except, DCSA and preclinical neurologic pathological condition. The DCSA were 73.54±15.00, 117.63±31.58, 171.25±99.56 and 175.00±94.83 (P<0.05), respectively. The PNGS were 3±0, 3±0, 4±0 and 4±0 (P<0.01), respectively. Conclusion: Finally based on this clinical study, it is recommended that postoperative recovery greatly depends on DCSA and PNGS in IVDD dogs. http://doi.org/10.5455/javar.2018.e261